Advances in Forming, Machining and Automation Proceedings of AIMTDR 2018 - Shunmugam, M. S.; Kanthababu, M. (Lecture Notes on Multidisciplinary Industrial Engineering,, 2019)
This volume comprises select proceedings of the 7th International and 28th All India Manufacturing Technology, Design and Research conference 2018 (AIMTDR 2018). The papers in this volume focus on forming and machining, and discuss both conventional technologies and the latest developments and innovations, including both experimental studies and simulations; while those on automation present the latest research on hardware as well as software aspects. This volume will be of interest to researchers, and practicing engineers alike.